Racialized and Gendered Disparities in Occupational Exposures Among Chinese and White Workers in Toronto - Premji, Stephanie; Lewchuk, Wayne (Ethnicity & Health, 2014)
Objective: We examined disparities in hazardous employment characteristics and working conditions among Chinese and white workers in Toronto, Canada.Design. We used self-administered questionnaire data from a 2005–2006 population-based survey (n = 1611). Using modified Poisson regression, we examined the likelihood for Chinese workers of experiencing adverse exposures compared to whites. Models were stratified by sex and adjusted for differences in human capital. Work sector was conceptualized as a mediating variable.Results. Chinese workers were generally more likely to report adverse exposures. In many cases, disparities were only evident or more pronounced among women. The shorter length of time in Canada of Chinese relative to whites accounted for some of the observed disparities. Meanwhile, the higher educational level of Chinese compared to whites provided them with no protection from adverse exposures. The risk of experiencing discrimination on the labor market and at work was more than 50% higher among Chinese men and women as compared to whites, and those disparities, though reduced, persisted after adjustment for confounders.Conclusions. Discrimination is far more prevalent among Chinese than among whites and may explain their disproportionate exposure to other hazards.
Keywords: Canada; Chinese; discrimination; ethnicity; gender; occupational health or hazards